Influencia de la actividad agrícola doméstica en la calidad de agua para uso doméstico del acuífero subterráneo en el distrito de Yantalo - Cordova Peña, Janet (2013)
The occurrence of natural events and the influence of anthropogenic activities can. affect the aquatic environment in particular to the bodies of superficial water (rivers, lagoons, lakes, seas, etc.). The quality cf the grcundwater is asscciated predcminantly with the soil physicochemical characteristics that act as a filter and in most cases has little variabilit-; in tlteir quality, on the cther ha..'ld the superficial waters are expcsed to a wide range of factors that can alter the quality of the water to different levels of intensity and with simple or complex alterations. Changes in the present of the surface water can occur due to the influence of multiple factors, within which are domestic activities, industrial, mining, agricultural, etc., which pollute the water with chemical and biological waste. In this way, in certain cases the water becomes unfit for human consumption or for other applications, such as agriculture, animal husbandry, industry, recreation and protection of aquatic life. Water pollution is one of the most serious problems in modern cities and their main agent polluter is the own people through domestic and farm waste. The present thesis work; "The influence of domestic and agricultura! activity in the water quality for domestic use ofthe underground aquifer, in the Yantalo District -2012 " . ,is te monitor the physical parameters chemical and bacteriological and then establish a comparison of the results with reference val u es recommended by the legal rules of the Environmental Qualit-; Standards for human consumption water according to the category A-1 that are those waters that can be reported with disinfection. The work was realized in Yantalo District, Moyobamba Province and San Martín Department. For the evaluation ofthe above mentioned study, it was chosen todo three calicatas to be able to confirm the level of pollution with regard to the aquifer underground, which dimensicns ofthe mentioned calicatas are: Calicata N°0l (L: lm x A: lm x Hb: 2m), Calicata N°02 (L: lm x A: lm x Hb H: 2m), Calicata N°03 (L: lm x A: lm x Hb: 2rn) , with a separation distance of two meters (2m) each, in a cross with respect to the underground aquifer, located in the Yantalo district. For the monitoring ofthe s~pk ca~tuie~ it .. was established every two weeks for three months ofthe 2012 year (October to December), following the established protoeols. Four stations have been monitored: Point 01: In the aquifer underground, point 02: Calicata N°0 1, point 03: Calicata N°02, point 04: Calicata N°03. Where t.l}ere appear t.l}e values to determine every physical, chernical, biological and rnicrobiological parameter of the stations mentioned in relation \vith the Sta11dards of Water quality (ECA) according to supreme Decree N°002-2008-MINAM. In global terms the Quality of water Jndex of 61.09;- is constituted as environmental indic.ator, in the development of water resources Ecomarmgement, in undergrou.11d aquifer and the three Calicatas. The index ofWater Quality of 61.09, in the underground aquifer lets you assign it toa The Index of \Vater quality of 61.09, in the underground aquifer it allows to assign a category of regular Quality. Key words: underground aquifer, environmental indicator.